1993
DOI: 10.2166/wst.1993.0622
|View full text |Cite
|
Sign up to set email alerts
|

Binding and Mobilization of Heavy Metals in Contaminated Sediments Affected by pH and Redox Potential

Abstract: In a contaminated sediment from Hamburg harbour, acid production, mobilization of Cu, Zn, Pb, and Cd at different redox- and pH-conditions, and the transfer and change of those particle bound metals are studied. During oxidation the pH value in the sediment suspension decreases from about 7 to 3.4 because of the low acid neutralization capacity (ANC). This leads to a mobilization of heavy metals whereby Cd and Zn as distinguished from Cu and Pb are strongly released. Also a change in particulate phase specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
254
1
27

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 497 publications
(296 citation statements)
references
References 0 publications
9
254
1
27
Order By: Relevance
“…In the industrial area, the values of pH changed from 6.98 to 7.41 with an average value of 7.13 in autumn, and the corresponding data were 7.22-7.91 and 7.6 in autumn, respectively. pH is the dominating mobilizing factor for metals in sediments (Calmano et al 1993). It is reported that decomposition of organic matter may lead to decrease the value of pH due to the formation of humic acid (Nobi et al 2010) and consequently increase the metal release.…”
Section: Resultsmentioning
confidence: 99%
“…In the industrial area, the values of pH changed from 6.98 to 7.41 with an average value of 7.13 in autumn, and the corresponding data were 7.22-7.91 and 7.6 in autumn, respectively. pH is the dominating mobilizing factor for metals in sediments (Calmano et al 1993). It is reported that decomposition of organic matter may lead to decrease the value of pH due to the formation of humic acid (Nobi et al 2010) and consequently increase the metal release.…”
Section: Resultsmentioning
confidence: 99%
“…The leached amount of Cu, Pb, and Zn, which were 10.4mg/L, 1.6mg/L and 9.85mg/L respectively, greatly below the permitted limits of Chinese EPA standard [16]. It has been reported that heavy metals locked with silica matrix could be hardly leached out under natural environment [17]. Therefore, the SCWO treatment could remain heavy metals in stable tailings which greatly reduce the leachability of heavy metals.…”
Section: Transformation Of Heavy Metalsmentioning
confidence: 92%
“…However, Cu concentration did not increase with increasing salinity, which was probably due to the complex interactions of salinity and other environmental factors (such as sediment moisture and pH). A drop in pH prevents the transfer of most trace metals from the water phase to the sediment and/or causes desorption from the sediments (Calmano et al 1993). Samecka-Cymerman and Kenpers (2001) also found that the concentrations of heavy metals in water and soil were usually negatively correlated with pH.…”
Section: Variations Of Heavy Metals In Plants and Sedimentsmentioning
confidence: 99%